2021
DOI: 10.1017/s0714980821000441
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words: How COVID-19 Has Impacted the Well-Being of Persons Living with Dementia in the Community

Abstract: COVID-19 has had a devasting impact on older adults in Canada, including persons living with dementia. This intrinsic case study sought to understand the perceptions of persons living with dementia regarding how COVID-19 has impacted their well-being. Ten persons living with dementia participated in in-depth qualitative interviews about their experience with COVID-19. Using thematic analysis, four themes were identified: (1) expressing current and future concerns; (2) social connections and isolation; (3) adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Other research highlights similar feelings of restriction, boredom, and isolation among people with intellectual disabilities during this time [10,[20][21][22]. Other vulnerable communities, such as people with chronic health conditions and older people, were similarly affected [23][24][25]. This suggests that vulnerable groups were disproportionally affected by the restrictions.…”
Section: Discussionmentioning
confidence: 91%
“…Other research highlights similar feelings of restriction, boredom, and isolation among people with intellectual disabilities during this time [10,[20][21][22]. Other vulnerable communities, such as people with chronic health conditions and older people, were similarly affected [23][24][25]. This suggests that vulnerable groups were disproportionally affected by the restrictions.…”
Section: Discussionmentioning
confidence: 91%
“…However, these stereotypes and opinions are problematic because they spread false information, harmful assumptions, and homogenize people living with dementia. Accordingly, McAiney and colleagues note that it is important to recognize that people with dementia are diverse and experience the COVID-19 pandemic differently depending on their unique context and abilities ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research described structural stigma related to inequitable access to health services and supports for people living with dementia during COVID-19. More specifically, these challenges included disparate access to respite services ( 22 ), social support ( 24 , 26 ), physicians, acute care services, and hospital care ( 23 , 34 ). Disparate access to care and support was especially problematic during COVID-19 lockdowns for people living with dementia in institutional settings.…”
Section: Resultsmentioning
confidence: 99%
“…14 A Canadian interview study with 10 people living with dementia found they were worried about contracting COVID-19 as well as losing contact through program closure, plus concern for the wellbeing of people newly diagnosed with dementia or living alone. 15 However, two Canadian surveys conducted early in the first lockdown in 2020 found lower levels of loneliness among older adults than younger ones. In their survey of 3,012 Englishspeaking Canadian adults (over 18 years of age), conducted between May 8 and June 23, 2020, Wickens and colleagues found greater odds of loneliness among all groups under 60 years of age, compared to those over 60 (5.5%) with the highest odds in the 18-29 years age group (13.8% 16 ).…”
Section: Understanding the Difference Between Social Isolation And Lo...mentioning
confidence: 99%
“…14 A Canadian interview study with 10 people living with dementia found they were worried about contracting COVID-19 as well as losing contact through program closure, plus concern for the well-being of people newly diagnosed with dementia or living alone. 15…”
Section: Introductionmentioning
confidence: 99%